PENGARUH BENTUK NOTCH TERHADAP KURVA HISTERISIS BAHAN FEROMAGNETIK NANOWIRE - W. Nursiyanto; B. Soegijono; E. Djatmiko (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Spintronic devices and data storage which based on magnetic usually made from material of ferromagnetic nanowire. The shape and size of the hysteresis for a ferromagnetic material have a very important meaning in its application on data storage devices. In this research has investigated hysteresis of a ferromagnetic material (Fe, Ni and Co) nanowire which has been given of doubles notch symmetrically in the middle of the nanowire with the shape are triangles and arches. Dimensional of nanowire size is 2000 × 200 × 5 Nm3 with a cell size of 2.5 × 2.5 × 2.5 Nm3 and the factor of damping is 0.01. The simulation of micromagnetic has been observed with uses software called Object Oriented Framework Micromagnetic (OOMMF) that based on equations of magnetic spin dynamics Landau-Lifshitz-Gilbert (LLG) The initial condition type of structure domain wall (DW) has been given with shape transverse-wall (TW) in the middle of the notch by the configuration of head-to-head. And then nanowire has been given external magnetic field with direction of the x-axis started from -150 mT to 150 mT to get hysterisis curve. The result shows that the shape of notch does not affect the hysteresis curves of ferromag. Keywords: ferromagnetic, nanowire, notch, oscillations, micromagnetic.